Peopling Global Health - João Biehl; Adriana Petryna (Universidade de São Paulo, 2014)
The field of Global Health brings together a vastly diverse array of actors working to address pressing health issues worldwide with unprecedented financial and technological resources and informed by various agendas. While Global Health initiatives are booming and displacing earlier framings of the field (such as tropical medicine or international health), critical analyses of the social, political, and economic processes associated with this expanding field - an "open source anarchy" on the ground - are still few and far between. In this essay, we contend that, among the powerful players of Global Health, the supposed beneficiaries of interventions are generally lost from view and appear as having little to say or nothing to contribute. We make the case for a more comprehensive and people-centered approach and demonstrate the crucial role of ethnography as an empirical lantern in Global Health. By shifting the emphasis from diseases to people and environments, and from trickle-down access to equality, we have the opportunity to set a humane agenda that both realistically confronts challenges and expands our vision of the future of global communities.